2018
DOI: 10.1038/nature25775
|View full text |Cite
|
Sign up to set email alerts
|

A suppression of differential rotation in Jupiter’s deep interior

Abstract: Jupiter's atmosphere is rotating differentially, with zones and belts rotating at speeds that differ by up to 100 metres per second. Whether this is also true of the gas giant's interior has been unknown, limiting our ability to probe the structure and composition of the planet. The discovery by the Juno spacecraft that Jupiter's gravity field is north-south asymmetric and the determination of its non-zero odd gravitational harmonics J, J, J and J demonstrates that the observed zonal cloud flow must persist to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
219
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(232 citation statements)
references
References 41 publications
11
219
1
1
Order By: Relevance
“…Guillot et al 3 (page 227) confirmed the 3,000-kilometre depth reported by Kaspi and colleagues using the symmetrical component of Jupiter's gravitational field. They demonstrate that, below this depth, the planet's interior rotates as a solid body, despite its fluid nature.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Guillot et al 3 (page 227) confirmed the 3,000-kilometre depth reported by Kaspi and colleagues using the symmetrical component of Jupiter's gravitational field. They demonstrate that, below this depth, the planet's interior rotates as a solid body, despite its fluid nature.…”
supporting
confidence: 75%
“…If Angela knows Emmanuel is cooperative because she and Emmanuel have interacted before, her reciprocity is direct. If she has heard from others that Emmanuel is a cooperative person, her reciprocity is indirect -a mechanism of particular relevance to human societies 3 .…”
Section: H a R L E S E F F E R S O N And E R N St F E H Rmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis by Kaspi et al (2018), based on the equatorially antisymmetric gravity moments J 3 to J 9 measured by the Juno mission , concludes that the wind speed must be significantly reduced at about 3,000 km depth, which corresponds to about 0.96 r J . This conclusion is supported by new interior models based on Juno data (Guillot et al, 2018). Kong et al (2018), however, point out that the problem is nonunique and that the gravity signal could also be explained by deeper reaching but weaker zonal flows that may not reflect zonal jets observed at cloud level.…”
Section: Introductionmentioning
confidence: 72%
“…In order to explore the range of gravity solutions consistent with the measurements we first construct interior models of Saturn that fit the observational constraints of Saturn's radius and gravity harmonic J 2 , under the assumption that the interior of the planet rotates as a RB following the methodology of Guillot et al (), which was effectively used for the analysis of Juno‐based Jupiter gravity field. Since J 2 is also affected by differential rotation (Galanti & Kaspi, ), we allow the RB solution to deviate from the measured value within the range J2RB=J2obs±50×106, to cover a wide range of differential rotation scenarios corresponding to different rotation rates and depths of the zonal flows (Galanti & Kaspi, ).…”
Section: The Rigid‐body Gravity Fieldmentioning
confidence: 99%